أثر استخدام برنامج تعليمى فى تنمية مهارات الحاسوب لدى الاطفال المعاقين عقليا - القمش، مصطفى نوري مصطفى; الجوالدة، فؤاد عيد (الجامعة الأردنية - عمادة البحث العلمي, 2012)
استهدفت الدراسة الحالية استقصاء أثر استخدام برنامج تعليمي في تنمية مهارات الحاسوب لدى الأطفال المعاقين عقلياً، وبلغت عينة الدراسة (40) طفلاً وطفلة، من الملتحقين في مركز المنار للتنمية الفكرية في عمان في الفصل الثاني للعام الدراسي (2010/2011)، وتتراوح أعمارهم الزمنية ما بين (8-15) سنة بمتوسط عمر زمني يبلغ (12.16) سنة، وبانحراف معياري مقداره (1.79)، حيث اختارهم الباحثان قصدياً، وتم توزيعهم عشوائياً على مجموعتين تجريبية وضابطة، درست المجموعة التجريبية المكونة من شعبتين (واحدة للذكور والأخرى للإناث) باستخدام برنامج تعليمي لتنمية مهارات الحاسوب، ودرست المجموعة الضابطة المكونة من شعبتين (واحدة للذكور والأخرى للإناث) بالطريقة الاعتيادية.ولتحقيق أهداف الدراسة قام الباحثان ببناء برنامج تعليمي لتنمية مهارات الحاسوب وقائمة الملاحظة المدرسية، وقد أشارت النتائج الى وجود فروق ذات دلالة إحصائية عند مستوى الدلالة (a =0.05) على اختبار قائمة الملاحظة المدرسية لصالح المجموعة التجريبية، كما أظهرت النتائج عدم وجود فروق جوهرية ذات دلالة إحصائية عند مستوى الدلالة (a 0.05=) تعزى لمتغيري الدراسة: (الجنس، والمتغير التفاعلي ((أسلوب التدريس × الجنس)). وتوصي الدراسة بإجراء المزيد من الدراسات واستهداف متغيرات أخرى غير تلك الواردة في الدراسة. The study aimed at investigating the effectiveness of educational program In the development of computer skills to children with mental retardation. The study consisted of (40) children with Mental Retardation, who are the learning at the center of Al-Manar to the intellectual development in the area of Amman and who enrolled for the second semester (2010\\2011). Their age ranged between (8-15) years with an average age of (12.16) years and standard deviation of (1.79). They were chosen for the study the sample of direct way, They were divided into two groups which are experimental and controlled. The experimental group that contains two sections (male and female) studied using a training program for Development of Computer Skills. The controlled group, consisting of two sections (males and females) studied by the traditional way. To achieve the objectives of the study, the researcher's initiated a training program for Development of Computer skills and using school environment observation lists. The study found that there were statistically significant differences at level ( =0.05) in the school environment observation lists for the benefit of the experimental group that was exposed to the educational program for the development of computer skills. Also, the results showed there are no significant differences at the significance level ( =0.05) between the averages for improving computer skills in children mentally retarded to respond dimensional due to the variables of the study (sex and variable of (Interactive teaching style × sex)). Based on the results of the study, the researchers recommends to carry out more studies.
Keywords: البرامج التعليمية -- تكنولوجيا التعليم -- تعليم ذوى الاحتياجات الخاصة -- التربية الخاصة -- التخلف العقلى -- الاطفال المعوقون -- الحاسبات الالكترونية